2021
DOI: 10.3390/ph14080766
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in Dogs and Cats: An Innovative Approach to Neoplastic and Non-Neoplastic Diseases

Abstract: Exosomes are extracellular vesicles with a diameter between 40 and 120 nm, which are derived from all types of cells and released into all biological fluids, such as blood plasma, serum, urine, breast milk, colostrum, and more. They contain proteins, nucleic acids (mRNA, miRNA, other non-coding RNA, and DNA), and lipids. Exosomes represent a potentially accurate footprint of the miRNA profile of the parental cell and can therefore be proposed as potential and sensitive biomarkers, both in diagnosing and monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
2
18
0
Order By: Relevance
“…Some of these studies have proposed the use of EVs (exosomes and/or microvesicles) as alternative biomarkers since concentrations of EVs can inform circulating inflammatory mediators in humans and dogs. Such a strategy has been shown to be valuable in evaluating organ functions based on exosome concentrations in blood 17,30 . In parasitic infections, EVs produced by parasites stimulate the host immune system to produce EVs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these studies have proposed the use of EVs (exosomes and/or microvesicles) as alternative biomarkers since concentrations of EVs can inform circulating inflammatory mediators in humans and dogs. Such a strategy has been shown to be valuable in evaluating organ functions based on exosome concentrations in blood 17,30 . In parasitic infections, EVs produced by parasites stimulate the host immune system to produce EVs.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, most studies have focused on the role of canine EVs (Can‐EVs) since these nanoparticles can contribute to cancer progression 28–30 . In humans, studies have shown the perspectives on the clinical use of exosomes as biomarkers for various diseases such as different kinds of cancers, Alzheimer's disease, infectious diseases, and others 31–34 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baier et al provided evidence that the amounts of miRNAs absorbed from milk are sufficient to alter human gene expression, i.e., miRNAs from one mammalian species can affect gene networks in another species ( Zhou et al, 2012 ; Baier et al, 2014 ). Milk exosomes increase the stability of miRNAs, which facilitates their absorption through the digestive tract ( Aarts et al, 2021 ; Diomaiuto et al, 2021 ; Gao et al, 2021 ; Marsh et al, 2021 ; Wehbe & Kreydiyyeh, 2021 ) . Animal and plant miRNAs are detected in all foods irrespective of processing ( Dever et al, 2015 ; Benmoussa and Provost, 2019 ; Mar-Aguilar et al, 2020 ; Melnik et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how EVs can act in physiology and pathology of animals could be of great importance in the whole picture of EV research. Moreover, animals and humans show similar physiology and share several diseases, such as cancer, making animals also good spontaneous and inducible models for human research [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%